Análise variacionista de /R/ na coda silábica medial no português falado em Alagoas - Lima, Jeylla Salomé Barbosa dos Santos (2019)
Based on the theoretical-methodological approach of Variationist Sociolinguistics (LABOV, 2008 [1972]), this thesis describes the segment / R / in the variety of Brazilian Portuguese spoken in Alagoas in an internal coda position. Its main objective is to describe the sociolinguistic behavior of this segment, by taking into account an a priori observation and previous works that describe four possible realizations in this variety: the glottal fricative, as in [pɔhtɐ] 'door'; the deletion, as in [sivisʊ] 'service'; a production that we are considering a type of approximant, as in [kɔɹdɐ] 'rope'; and the tap [poɾkʊ] 'pig'. The corpus is constituted by excerpts of spontaneous speech of 144 individuals born in the cities of Arapiraca, Delmiro Gouveia, Maceió, Santana do Ipanema, São Miguel dos Milagres and União dos Palmares, distributed according to the following context variables: antecedent context, tonicity, word size and lexical item, adding to these the social variables sex / gender, age group, levels of education, city and individual. The variants were submitted to statistical analysis, in which the percentage of achievement of each one, in each city, was related to the linguistic and social variables that influenced them, thus verifying if the outlined frames can be interpreted as indication of a stable change or change in progress. The results point to the following situations: i) the tap is an moribund variant, due to its scarce appearance in the data (only 26 cases occurred throughout the corpus), with less than 1% of production, and occurring only within the elderly; (ii) deletion is favored by the linguistic variable following context - [+continuous -sonorant], as 0.97 of relative weight for the consonants of [+continuous] and the following [noncoronal] context, with relative weight equal to 0.61-, by the interaction between the variables education and city, showing interference in the cities of São Miguel dos Milagres and União dos Palmares, because, in these cities, the higher the education, the lower the deletion, becoming a case of stable variation. The gender variable also plays a role, as the result showed that men favor deletion, with a relative weight equal to 0.59. The result for the variables lexical item and individual showed that the interference of these is high: 56.9% and 44.8% respectively; (iii) the approximant occurs only in the presence of consonants with the [+obstruction -continuous] features, being strongly favored among them by the coronal /t/ and /d/), while the results of the analysis of the social factors indicate that this variant is going through a linguistic change in progress with a tendency to disappear. Much of the variation observed in the data can be explained by the variation between individuals and lexical items. Regarding the approximant variable, individual showed a high interference, with 40.7% indicating that the variability can be explained by the variation between the individuals. In addition to the analysis considering the variation of the / R /, a phenomenon also observed was the palatalization of the occlusives / t, d / after the variant approach, which led us to undertake a complementary investigation, which came to the following results: there is an inexpressive variation between the lexical items. The variation in the social level is sufficiently explained by the variables age and city. Although the frequency of palatalization is high, the variant is in disuse in Alagoas.